SEJARAH MASUKNYA ISLAM DI INDONESIA - Ahmad Hapsak Setiawan; Roby Sagara (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2024)
The introduction of Islam to Indonesia is a complex historical event that took place over a long period of time, starting from the 7th century and reaching its peak in the 13th to 16th centuries. The process of Islamisation in the archipelago is marked by unique characteristics, namely a relatively peaceful and gradual spread, in contrast to the pattern of the spread of Islam in several other regions of the world. Islam entered through various channels, mainly trade, marriage and da'wah by Muslim traders, ulama and Sufis. Ports and coastal cities became the starting point for the spread of Islam, which then spread to inland areas. The process of Islamisation in Indonesia was also characterised by intensive adaptation and acculturation with local culture, resulting in a distinctive form of Islam in the archipelago. This accommodative approach allowed Islam to be widely accepted and become an integral part of the identity of Indonesian society. The introduction of Islam not only changed the religious landscape, but also shaped new social, political, and cultural dynamics that had a profound and lasting influence in the formation of Indonesia's national identity.